Trends in Singleton Breech Delivery in Rajavithi Hospital from 2002-2008 - Apithan Puangsricharern; Wahcharapot Anakrat (The Royal Thai College of Obstetricians and Gynaecologists, 2012)
Objectives: To determine the trends in management of pregnant women with breech presentation in Rajavithi Hospital and prognostic factors related to neonatal outcomesMaterials and Methods: A retrospective descriptive study at Rajavithi Hospital from January 1st2002 to December 31st 2008. Obstetric database and medical records of pregnant women with singleton breech presentation, gestational age more than 28 wks were reviewed. Characteristics of pregnant women, gestational age, parity, type of breech, mode of delivery, maternal and neonatal outcomes were compared.Results:There were 1,585 women with singleton breech presentation gestational age more than 28 wks. Trend in singleton vaginal breech delivery was declining significantly from 30% to 10% (p<0.05). Conversely, trend in singleton cesarean section was increasing from 70% to 90% (p<0.05). In the neonates delivered by vaginal breech delivery compared with those delivered by cesarean section, there were some association with poor neonatal outcomes such as, low Apgar score at 1,5 min (p<0.001), NICU admission (p < 0.001), neonatal intubation (p<0.001), maternal hospital stay day (p<0.001). If the trend is not change, the cesarean section rate for breech presentation will approved equal 100% in 9.6 years (2012).Conclusions: Trends in vaginal breech delivery at Rajavithi Hospital had gradually declined.